Nafamostat Mesilate, a Broad Spectrum Protease Inhibitor, Modulates Platelet, Neutrophil and Contact Activation in Simulated Extracorporeal Circulation - Sundaram, Sumuk; Gikakis, Nicolas; Erik Hack, C; Niewiarowski, Stefan; Edmunds, L H, Jr; Koneti Rao, A; Sun, Ling; Cooper, S L; Colman, Robert W (Thrombosis and Haemostasis, 1996)
Activation of humoral and cellular participants in inflammation enhances the risk of postoperative bleeding and multiple organ damage in cardiopulmonary bypass (CPB). We now compare the effects of heparin alone in combination with nafamostat mesilate (NM), a protease inhibitor with specificity of trypsin-like enzymes, in an extracorporeal circuit which simulates CPB. NM significantly inhibits the release of platelet (β-thromboglobulin (βTG) at 60 and 120 min. Platelet counts do not differ. ADP-induced aggregation decreases in circuits with NM, which is due to a direct effect of NM on platelet function. NM prevents any significant release of neutrophil elastase; at 120 min, plasma elastase-α1antitrypsin complex is 0.16 μg/ml in the NM group and 1.24 μg/ml in the control group. NM completely inhibits formation of complexes of C1 inhibitor with kallikrein and FXIIa. NM does not alter markers of complement activation (C1-C1-inhibitor complex and C5b-9), or indicators of thrombin formation (F1.2). However, at 120 min, thrombin activity as measured by release of fibrinopeptide A is significantly decreased. The data indicate that complement activation during CPB correlates poorly with neutrophil activation and that either kallikrein or FXIIa or both may be more important agonists. The ability of NM to inhibit two important contact system proteins and platelet and neutrophil release raises the possibility of suppressing the inflammatory response during clinical CPB.